STRATIFIKASI SOSIAL DI KELURAHAN SEKIP KECAMATAN LIMAPULUH KOTA PEKANBARU - Alfian, Yudi; Tantoro, Swis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Social stratification is a symptom of a general nature in every society. The Forms ofdifferent walks of life and a lot of layers is that exist, even in capitalist society, democratic,communist, and so onc. The different walks of life wasexisted since human society to know theirlife together in a social organization.The purpose of this study was (1) to determine how the level of social stratification thatexisted at the sub-district Limapuluh of Sekip villages and (2) to determine the factors that affectsocial change in the village of Sekip. This study was expected to be as one means oftransforming ideas and gain knowledge as well as a writer and contributed information in thethinking that led to the study of social discourse particularly closely linked in social stratificationcommunity in the development of residential and educational environment. This study took placeon January to April 2015. This study used descriptive qualitative research methods that explainedand interpreted the collected of data. The data were collected by observation and interview.Technique data validity checking was done by the extension of participation and triangulation.The results of this study indicated that social stratification can form in people who have aregular order of life. As long as there was something considered valuable in the society, then itwould be a valuable element that caused the formation of social stratification. Theforms of socialstratification that occurs in the Sekip Village Subdistrict of Limapuluh of Pekanbaru was thestratification of wealth element. The Social was changing that occured in society Sekip villagescaused by several factors.From internal factors, the social changes caused by changed inpopulation and discoveries (innovation) new. While external factors, the social change Sekipcaused by changed in the physical environment as well as the influence of other cultures.Keywords: Stratification, Layers, Social